Inflammatory Monocytes Are Rapidly Recruited to the Post-Ischaemic Liver in Patients Undergoing Liver Transplantation and Cytokines Associated with Their Activation Correlate with Graft Outcomes - Francis P. Robertson; Antonia O. Cuff; Victoria Male; Graham P. Wright; Laura J. Pallett; Barry J. Fuller; Brian R. Davidson (Current Issues in Molecular Biology)
Liver ischaemia–reperfusion (IR) injury remains a major cause of morbidity and mortality following liver transplantation and resection. CD4+ T cells have been shown to play a key role in murine models; however, there is currently a lack of data that support their role in human patients. Methods: Data on clinical outcomes and complications were documented prospectively in 28 patients undergoing first elective liver transplant surgery. Peripheral blood samples were collected at baseline (pre-op), 2 h post graft reperfusion, immediately post-op, and 24 h post-op. A post-reperfusion biopsy was analysed in all patients, and in five patients, a donor liver biopsy was available pre-implantation. Circulating cytokines were measured, and T cells were analysed for activation markers and cytokine production. Results: Circulating levels of cytokines associated with innate immune cell recruitment and activation were significantly elevated in the peri-transplant period. High circulating IL-10 levels corresponded with the development of graft-specific complications. The proportion of CD4+ T cells in the peripheral circulation fell throughout the peri-operative period, suggesting CD4+ T cell recruitment to the graft. Although TNFα was the predominant cytokine produced by CD4+ T cells in the intrahepatic environment, the production of IFNγ was significantly upregulated by circulating CD4+ T cells. Furthermore, we demonstrated clear recruitment of inflammatory monocytes in the peri-operative period. In donor-and-recipient pairs with a mismatch at the HLA-A2 or A3 allele, we demonstrated that inflammatory monocytes in the liver are recipient-derived. Discussion: This is the first study to our knowledge that tracks early immune cell responses in humans undergoing liver transplantation. The recruitment of inflammatory monocytes from the recipient and their cytokine release is associated with liver-specific complications. Inflammatory monocytes would be an attractive target to ameliorate ischaemia–reperfusion injury.